Biological Activities of Albizia spp. - จ้อยชะรัด นันทิยา; ลิ้มสุวรรณ สุรศักดิ์ (KKU Science Journal, 2013)
The genus Albizia belongs to the family Leguminosae-Mimosoideae. Several species of Albizia have been used in folk medicine both in Thailand and other countries for the treatment of many ailments. The plants in this genus are sources of secondary metabolites with biological activities, many of which are useful in pharmaceuticals and medicine. This genus posseses several pharmacological activity such as cytotoxicity against human cancer cell line, antiinflammatory, antioxidant, antimicrobial, and antiparasitic activities. Triterpene saponins, spermine alkaloids, and flavonoids are the main active components of this genus. Some of these components have a potential to be developed into new drug. Therefore, this review will focus on the biological activities and active compounds from the genus Albizia.